2004
DOI: 10.1016/s0095-4470(03)00039-1
|View full text |Cite
|
Sign up to set email alerts
|

On the phonetics and phonology of “segmental anchoring” of F0: evidence from German

Abstract: We measured the alignment of F0 minima and maxima with segmental landmarks, in prenuclear rising accents in Northern and Southern German. As in earlier studies of other languages, we found consistent patterns of alignment. Both Northern and Southern German speakers align rises later than published data for Greek, English, and Dutch; Southern German speakers show later alignment than Northern speakers. The differences are small but significant. Moreover, native patterns of alignment are carried over into the Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
250
2
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(273 citation statements)
references
References 15 publications
15
250
2
6
Order By: Relevance
“…Atterer and Ladd (2003) found gradient differences in the alignment of prenuclear rises, both across varieties (Northern vs. Southern German) and across languages (German vs. English). They therefore suggested the existence of a single category of rising accent, even though tonal target alignment can vary along a continuum across languages and varieties of the same languages due to language-specific phonetic implementation rules.…”
Section: Resultsmentioning
confidence: 89%
“…Atterer and Ladd (2003) found gradient differences in the alignment of prenuclear rises, both across varieties (Northern vs. Southern German) and across languages (German vs. English). They therefore suggested the existence of a single category of rising accent, even though tonal target alignment can vary along a continuum across languages and varieties of the same languages due to language-specific phonetic implementation rules.…”
Section: Resultsmentioning
confidence: 89%
“…Sendo assim, os extremos fonéticos coincidem com os extremos geográficos, sendo observada uma maior distância no alinhamento do Norte em relação ao Sul. Semelhante tipo de variação temporal também foi descrito para variedades do Norte e do Sul da Alemanha (Atterer & Ladd, 2004): nas variedades do Norte, foi observado um alinhamento mais adiantado em relação à variedade do Sul. Assim como observado para o PB, as diferenças no alinhamento dos tons exibem pequenas distâncias temporais, a qual sugere uma variação gradual no alinhamento entre as variedades.…”
Section: Todas As Regiõesunclassified
“…As far as L2 intonation is concerned, previous studies have found that when marking information structure, non-native speakers transfer their L1 focus-projection rules (e.g., Zubizaretta & Nava, 2011) and the L1 intonational patterns, even at a high level of proficiency (Kelm, 1987;McGory, 1997;Nguyên, Ingram, & Pensalfini, 2008;Rasier & Hiligsmann, 2007;Swerts & Zerbian, 2010;Ueyama & Jun, 1998 among others). From the literature on L2 intonation, it is also well established that L1 transfer can affect more fine-grained aspects of the prosodic structure, such as the phonetic implementation of identical phonological pitch movements (e.g., Atterer & Ladd, 2004;Gut, 2009;Mennen, 2004).…”
Section: Introductionmentioning
confidence: 99%